2009
DOI: 10.1002/aic.11974
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of multiwalled carbon nanotubes on Al2O3 supported Ni catalysts in a fluidized‐bed

Abstract: Multiwalled carbon nanotubes (MWNTs) were synthesized on Al 2 O 3 supported Ni catalysts from C 2 H 2 and C 2 H 4 feedstocks in a fluidized bed. The influence of the ratio of superficial gas velocity to the minimum fluidization velocity (U/U mf ), feedstock type, the ratio of carbon in the total quantity of gas fed to the reactor, reaction temperature, the ratio of hydrogen to carbon in the feed gas, and nickel loading were all investigated. Significantly, the pressure drop across the fluidized-bed increased a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…For the purpose of this work, the stages of material acquisition and product manufacturing will be collectively referred to as “manufacturing”. The LCI data corresponding to production of the metal catalyst and synthesis of CNTs are based on the carbon deposition yields (CDYs) and synthesis reaction yields (SRYs) reported in Fazle-Kibria et al, Leone, and Liu and Harris for the use of acetylene with a bimetallic nickel and iron catalyst supported on aluminum oxide. CNTs produced via bimetallic catalyst systems have shown the ability to generate higher field emission efficiencies than those synthesized via monometallic catalytic systems .…”
Section: Life Cycle Assessment Methodsmentioning
confidence: 99%
“…For the purpose of this work, the stages of material acquisition and product manufacturing will be collectively referred to as “manufacturing”. The LCI data corresponding to production of the metal catalyst and synthesis of CNTs are based on the carbon deposition yields (CDYs) and synthesis reaction yields (SRYs) reported in Fazle-Kibria et al, Leone, and Liu and Harris for the use of acetylene with a bimetallic nickel and iron catalyst supported on aluminum oxide. CNTs produced via bimetallic catalyst systems have shown the ability to generate higher field emission efficiencies than those synthesized via monometallic catalytic systems .…”
Section: Life Cycle Assessment Methodsmentioning
confidence: 99%
“…The SiNTs have been produced by a conventional CVD technique (at temperatures below the Si–Ni eutectic point). The use of Ni/Al 2 O 3 as catalyst for methane decomposition is a well-known route for the growth of CNTs. Also, metal nickel (and copper) substrates were shown to act as an effective catalyst for the decomposition of gaseous silane and germane precursors at a broad range of temperatures . We found that Ni/Al 2 O 3 , simply by dipping the AAO membrane in a Ni solution, served as an excellent catalyst for the chemical decomposition of silane onto the AAO pore surface, thus enabling the controllable formation of SiNTs.…”
mentioning
confidence: 86%
“…During the growth process, once SiH 4 starts to flow at a temperature of 450 °C, it reduces the absorbed Ni 2+ to form Ni Red /Al 2 O 3 clusters on the membrane surface or alternatively to form Ni x Si y (nickel silicide) crystalline clusters. The Ni Red /Al 2 O 3 (or NiSi/Al 2 O 3 ) clusters serve as catalysts for further SiH 4 decomposition resulting in absorption of Si onto the membrane’s nanochannel inner surfaces, in a manner similar to the decomposition of methane during CNT growth. The absorbed Si serves in turn to catalyze the decomposition of SiH 4 and encourages the continuous growth of the SiNTs. Nickel atoms can diffuse into the forming silicon layer, spreading evenly into the SiNT walls volume, at the growth temperatures between 450 and 650 °C.…”
mentioning
confidence: 99%
“…In 2009, Harris et al. [ 94 ] systematically studied the crucial factor of the ratio between superficial gas velocity and minimum fluidization velocity during the fluidization growth of MWCNTs. They discovered that as reaction time increased, pressure drop in the fluidized bed also increased.…”
Section: Fluidization and Mass Production Of Cntsmentioning
confidence: 99%